(untitled) (Veterinary Science, 2017)
On analysed the immunohstochemistry value as a method for adjusted the stadistic of bovine tuberculosis in La Pampa province of Argentine which was estimated trough the macroscopic diagnosis in the slaughterhouse inspection. On applicated the immunohistochemistry technique to the formol-fixed and paraffin-embedded tissu samples obtained in two back works. The macroscopic compatible lesions as tuberculosis were confirmed by bacteriology in an 50,33%, by histopathology in an 69,80% and by immunohistochemistry in an 72,49%. This positive difference in order to immunohistochemistry is attributed to the atypical tuberculosis granuloma morphology (an specific abscess). This work enhances the grate value of the gross inspection, trough this easy and rapid operative condition, but demonstrate the importance of the immunohistochemistry technique for the stadistic correction and for the epidemiological vigilance, trough regional samples.